Estilo intuitivo: uma possibilidade de tecnologia gerencial nas organizações públicas - Carvalho, Helenice Feijó de (2001)
The present dissertation alms at stimulating a reflection on the technological management evolution in public organizations, glVIng emphasis to an intuitive management style. From specialized researched literature reference, the author has given major importance to comment on the management theories based on Jungian typology. The study consists of: a summary of the historical evolution of management, a discussion on the meaning of the term intuition, a presentation of theories on management style and its importance in the making decision process, and an evaluation of the results obtained In research about the intuitive management style in organizations, In general, as well as in specific public ones.